Инженерный метод оценки массы выделившегося водорода при заряде тяговых аккумуляторных батарей - Polevoda, И.; Polevoda, Иван (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
The engineering method of an assessment of weight of the emitted hydrogen necessary for calculation fire danger category of compartment is offered.